Coronabedingte Ungleichheit und Armut in Deutschland: Überschätzt oder unterschätzt?; The rise of inequality and poverty in Germany during the pandemic: False alarm? - Michael Dauderstädt (Wirtschaftsdienst, 2022)
– Recent data from EU-SILC and Destatis seemed to indicate a dramatic increase in German inequality and poverty in the pandemic year 2020. But Destatis had changed its data collection method. Based on several studies, it is likely that the actual rise has been much weaker while the previous data collection by Destatis might have underestimated the true disparities within German society in the past.
Keywords: C81; D31; I32; 330; Einkommen; Armut; Coronavirus; Deutschland